Estimation of the Arctic aerosols from local and long-range transport using relationships between 210Pb and 212Pb atmospheric activity concentrations. (March 2015) - Zhang, Weihua; Chen, Jing; Ungar, Kurt; Cooke, Michael
Abstract: In this study, the aerosol activity concentrations of 210 Pb at 28 Canadian radiological monitoring stations from 2009 to 2013 were analyzed. The results show that the ratio of 210 Pb winter average concentration to summer average concentration increases with increasing latitude. This could be used to evaluate the transport of pollutants to the Arctic region such as the Arctic haze from Eurasia through long-range atmospheric transport during winter. Based on 12 years of monitoring results from the Yellowknife station that includes both 210 Pb and 212 Pb concentrations, the study confirms that the seasonal distribution of 210 Pb to 212 Pb activity concentration ratios has a significant peak in winter and a relatively low value in summer, which can be used as an indicator of the air mass flow to the Arctic. The period dominated by long-range aerosol transport and Arctic haze was estimated by fitting a Gaussian distribution function to the peak values of this ratio in winter. A peak width parameter of full width at half maximum (FWHM) allows a year by year estimate of the period of influence by long-range transport of aerosols, and this varied between 67 and 88 days in this study. The fitted Gaussian peak also shows that the season of the continental influenced air mass in Yellowknife usually starts in mid-to-late November and ends in mid-to-late April. Thus, the 210 Pb to 212 Pb ratio distributions may enable the determination of periods dominated by long-range aerosol transport and the scale of the Arctic haze at different latitudes. Highlights: Twelve years 210 Pb/ 212 Pb monitoring results from low to high altitude are presented. The 210 Pbwinter / 210 Pbsummer ratio increases clearly with latitude of monitoring site. The pollutant transport to the Arctic is estimated by distribution 210 Pb/ 212 Pb ratio. The time scale of long-range transport aerosol bearing 210 Pb to Arctic is reported.